2021
DOI: 10.1108/tqm-07-2021-0204
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating SMEs' profitability through total quality management: the roles of risk management, digitalization, stakeholder management and system deployment

Abstract: PurposeThis study investigates the effect of total quality management (TQM) on small and medium enterprises (SMEs) ' profitability by examining whether the new TQM dimensions of risk management, digitalization, stakeholder management and system deployment, facilitate the impact of traditional TQM dimensions on profitability.Design/methodology/approachA structured survey of 271 Finnish SMEs divided into industry companies and service companies was used.FindingsRisk management facilitates the relation between co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 78 publications
1
27
0
Order By: Relevance
“…By providing empirical evidence, the present paper not only advances research on SCRM in SMEs, which still is an underdeveloped field of research (Zeiringer et al, 2022), but it also contributes to the general study of RM in SMEs (e.g. Lepistö et al, 2021) by showing the need for focusing on the tradeoff between SCRM-related skills and organisational performance (here innovation performance). Moreover, this study has demonstrated that SCRM ability and SCRM maturity could have opposing implications on innovation performance, a finding that gives a more fine-grained understanding of SCRM in SMEs.…”
Section: Discussionmentioning
confidence: 83%
“…By providing empirical evidence, the present paper not only advances research on SCRM in SMEs, which still is an underdeveloped field of research (Zeiringer et al, 2022), but it also contributes to the general study of RM in SMEs (e.g. Lepistö et al, 2021) by showing the need for focusing on the tradeoff between SCRM-related skills and organisational performance (here innovation performance). Moreover, this study has demonstrated that SCRM ability and SCRM maturity could have opposing implications on innovation performance, a finding that gives a more fine-grained understanding of SCRM in SMEs.…”
Section: Discussionmentioning
confidence: 83%
“…As there is often no particular RM division or a risk manager, RM is taken care of by the general management or it is the SME owner's task [37]. However, applying a structured RM approach can, on the one hand, side help SMEs to overcome resource constraints and on the other hand side also increase their company profitability [38,39].…”
Section: Risk Management In Supply Chains In Smesmentioning
confidence: 99%
“…Such a notion can be integrated into future research when developing conceptual frameworks. Several studies support the notion that ISO 9001 is irrelevant in the economic sense (Ferreira and Cândido, 2021; Lepistö et al. , 2022).…”
Section: Discussionmentioning
confidence: 93%